Supporting Mathematics Teachers to Develop Jumping Task Using PISA Framework (JUMPISA) - Zulkardi Zulkardi; Ratu Ilma Indra Putri (Jurnal Pendidikan Matematika, 2020)
The new revision of Curriculum 2013 stresses mathematics literacy tasks that force students to use their higher-order thinking skills (HOTs) and collaborative learning. In the Lesson study for the learning community,  teachers deal with two kinds of problems: easy task or sharing and jumping task. This paper aims to report the process of training or professional development of mathematics teachers in Palembang in developing tasks, both sharing and jumping, using the PISA framework. This research used the development research method. Three main activities during the training are: Introducing what and why PISA items from 2000 – 2018; Developing PISA-items for jumping task; and The formative evaluation to measure teachers’ knowledge after training. Results show that mathematics teachers who follow the training can produce their items, share, and jump, using the PISA framework. To conclude, the task design training program using examples of PISA like can support teachers in developing their task, both sharing and jumping.